Increased interactivity and improvements to the GigaScience database, GigaDB. (11th February 2019) - Xiao, Si Zhe; Armit, Chris; Edmunds, Scott; Goodman, Laurie; Li, Peter; Tuli, Mary Ann; Hunter, Christopher Ian
Abstract: With a large increase in the volume and type of data archived in GigaScience Database (GigaDB) since its launch in 2011, we have studied the metrics and user patterns to assess the important aspects needed to best suit current and future use. This has led to new front-end developments and enhanced interactivity and functionality that greatly improve user experience. In this article, we present an overview of the current practices including the Biocurational role of the GigaDB staff, the broad usage metrics of GigaDB datasets and an update on how the GigaDB platform has been overhauled and enhanced to improve the stability and functionality of the codebase. Finally, we report on future directions for the GigaDB resource.